Hyaluronic acid/chitosan-coated poly (lactic-co-glycolic acid) nanoparticles to deliver paclitaxel and temozolomide for oral cancer cells - Hassn Ali, Mesrati Malak (2022)
Oral cancer has a poor survival rate despite comprehensive therapy. Conventional therapies may eliminate most of the tumour mass cells; however, they are leaving behind the oral cancer stem cells (OCSCs). Among these cells, an aggressive group capable of tumour initiating, self-renewal, invasion and metastasis resulting in tumour relapse and resistance, overexpressing the cancer stem cell (CSC) biomarker, cluster of differentiation 44 (CD44). Therefore, the discovery of a treatment strategy to enhance chemotherapeutic efficiency against oral cancer cells, mainly CD44+cells, is imperative. This study aims to synthesise and characterise hyaluronic acid/chitosan-coated poly (lactic-co-glycolic acid) nanoparticles and assess their effectiveness in delivering PTX and TMZ to oral cancer cells in terms of cell inhibition and apoptosis. This study also focused on assessing the coordinated administration of PTX and TMZ and whether they exhibit significant synergistic cell inhibition effects with reduced introduced drug concentration if co-delivered simultaneously. Additionally, to determine the potentially involved mechanisms by which the formulated drug-loaded nano-carrier induced cell apoptosis. Dynamic light scattering (DLS), high resolution-transmission electron microscopy (HR-TEM), field emission-scanning electron microscopy (FE-SEM), and Fourier transform infrared spectroscopy (FT-IR) were used to characterise the nanoparticles. Results of DLS show that the nanoparticles were successfully synthesised and had a promising nano-sized diameter of 260.40±11.54 nm, a positive zeta potential of +14.31±1.37 mV and a homogeneous distribution proven by a low polydispersity index value of 0.15±0.03. HR-TEM and FE-SEM results confirmed that nanoparticles are uniformed and spherical in structure with a size smaller than 100 nm. FT-IR spectra confirmed that polylactic-co-glycolic acid, chitosan and hyaluronic acid are all involved in nanoparticle formation. XTT assay manifested that PTX and TMZ, as well as their combination (PTX:TMZ), have inhibited the proliferation of CAL-27 oral cancer cell line with the half maximal inhibitory concentration of 4nM, 1000μM and 2nM:300μM respectively. XTT assay and xCELLigence real-time cell analysis revealed that compared to free drugs, the single-loaded drug and the co-loaded one induced more cytotoxicity. PTX and TMZ showed a considerable synergistic inhibitory effect on CAL- 27 cells. This effect was discovered to be more significant when the drugs were encapsulated in the nanoparticles. To examine the signs of cell death and cell cycle alteration induced by the drug-loaded nanoparticles, Annexin V-FITC assay and cell cycle arrest assay were performed. Both were followed by flow cytometry analysis. Apoptosis analysis verified that all drug-loaded nanoparticle groups demonstrated significantly higher apoptosis rates than their relative free drug groups. Cell cycle analysis indicated that free and loaded PTX resulted in causing the highest G2-phase arrest rates of 17.69% and 22.45% of cells, respectively. Treatment with free or loaded TMZ arrested higher cell proportion at S-phase, and the combination drug treatment groups showed the highest S-phase arrest rates among all groups. In order to determine the reactive oxygen species (ROS) levels induced by the treatment, a dihydroethidium assay was performed. Cells treated with single and dual PTX and TMZ possessed higher ROS levels than non-treated cells, and nanoparticles retained and modestly improved ROS levels induction. JC-1 assay revealed that loaded PTX and TMZ caused more vital green staining within the mitochondria than the free drugs did, indicating more mitochondrial collapse. The combination drug groups, especially the loaded drugs, exhibited more downward trend in the mitochondrial potential membrane than single drugs. Additionally, from an mRNA gene expression study, loaded single or dual drugs resulted in more upregulation in genes expression associated with DNA damage, mitochondrial collapse, cell apoptosis and MAPK signalling pathways. In conclusion, established nanoparticles could be considered a potential candidate for oral cancer therapy in the near future since they could deliver and improve the efficacy of single and dual drugs against oral cancer cells and induce cell cycle alteration and intrinsic mitochondrial-mediated apoptosis. In contrast, without drugs, it did not exert toxicity effects on the cells.